Demographics, Treatments, and Outcomes of Acute Respiratory Distress Syndrome: the Focused Outcomes Research in Emergency Care in Acute Respiratory Distress Syndrome, Sepsis, and Trauma (FORECAST) Study. Issue 5 (May 2020) - Fujishima, Seitaro; Gando, Satoshi; Saitoh, Daizoh; Kushimoto, Shigeki; Ogura, Hiroshi; Abe, Toshikazu; Shiraishi, Atsushi; Mayumi, Toshihiko; Sasaki, Junichi; Kotani, Joji; Takeyama, Naoshi; Tsuruta, Ryosuke; et al.
ABSTRACT: Purpose: Acute respiratory distress syndrome (ARDS) remains a major cause of death. Epidemiology should be continually examined to refine therapeutic strategies for ARDS. We aimed to elucidate demographics, treatments, and outcomes of ARDS in Japan. Methods: This is a prospective cohort study for ARDS. We included adult patients admitted to intensive care units through emergency and critical care departments who satisfied the American–European Consensus Conference (AECC) acute lung injury (ALI) criteria. In addition, the fulfillment of the Berlin definition was assessed. Logistic regression analyses were used to examine the association of independent variables with outcomes. Results: Our study included 166 patients with AECC ALI from 34 hospitals in Japan; among them, 157 (94.6%) fulfilled the Berlin definition. The proportion of patients with PaO2 /FIO2 ⩽ 100, patients under invasive positive pressure ventilation (IPPV), and in-hospital mortality was 39.2%, 92.2%, and 38.0% for patients with AECC ALI and 38.9%, 96.8%, and 37.6% for patients with Berlin ARDS, respectively. The area of lung infiltration was independently associated with outcomes of ARDS. Low–mid-tidal volume ventilation was performed in 75% of patients under IPPV. Glucocorticoid use was observed in 54% patients, and it was positively associated with mortality. Conclusions: Our study included a greater percentage of patients with ARDS with high severity and found that the overall mortality was 38%. The management of ARDS in Japan was characterized by high the utilization rate of glucocorticoids, which was positively associated with mortality. Abstract : Supplemental Digital Content is available in the text